New Fluorinated Tyrosinase Inhibitor from a Chemically Engineered Essential Oil - García, Paula (2016)
The generation of fluorinated essential oils as a source of bioactive compounds is described. Most of the components of the natural mixtures were altered, leading to the discovery of a new fluorinated tyrosinase inhibitor.